Pengaruh Likuiditas, Profitabilitas, Financial Leverage, dan Arus Kas Operasi Dalam Memprediksi Kondisi Financial Distress - Maretha Rissi, Dita; Amelia Herman, Lisa (Akuntansi dan Manajemen, 2021)
Financial distress occurs before the bankruptcy of a company. Thus the financial distress model needs to be developed, because by knowing the company's financial distress from an early age, it is hoped that actions can be taken to anticipate conditions that lead to bankruptcy. Financial distress can be measured through financial statements by analyzing financial statements. This study aims to determine and analyze the effect of liquidity, profitability, financial leverage, and operating cash flow in predicting financial distress conditions for manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. Data from the company's official website and completed from the IDX and ICMD websites. There are independent variables, namely liquidity, profitability, financial leverage, and operating cash flow, while the dependent variable in this study is financial distress. The data analysis method used in this research is logistic regression analysis method which aims to determine the role of each independent variable in influencing the dependent variable. The results of this study indicate that liquidity has no effect on financial distress, meaning that if the company is able to pay its debts well, then it is likely that the company will not experience financial distress. Profitability has no effect on financial distress, meaning that the size of the company's profit value has no effect on the company so that it avoids financial distress conditions. Financial leverage has a positive effect on financial distress, meaning that if the company has higher debt and is not followed by high sales results, it can allow failure to pay debts which causes the company to be in financial distress. Cash flow has no effect on financial distress, meaning that if the company has a good operating cash flow value, it will not experience financial distress.